كتاب البيوع من موطأ الإمام مالك برواية يحيى بن عبد الله بن بكير المخزومي : دراسة تحليلية مقارنة - بوالنعمة، فواد بن أحمد
This thesis addresses the chapter on sales from Imam Malik's Muwatta', narration of Yahya ibn Bukair, aiming to verify the accuracy and mastery of Yahya bin Bukair in his narrations, to demonstrate where his version stands amongst the other narrations of Al-Muwatta' and to highlight the financial transactions which were mentioned in the chapter on sales in Al-Muwatta'. It also links these transactions to contemporary financial instruments. The thesis adopted the descriptive comparative method and the analytical approach, whereby the researcher verified the wording of Yahya bin Bukair's narration, and then authenticated it by referring to other printed versions of Al-Muwatta as well as the famous books of Sunnah, containing hadith and athar by stating their ranks in terms of being authentic or weak (sahih or da'eif) and then comparing between these versions. It also specified the differences between them, followed by analysis, extracting the most important transactions mentioned in them, whether they were permissible or forbidden, by linking them to contemporary transactions and highlighting what might fall under modern applications. The most important finding of the research is that of the words used in different versions of Al- Muwatta. This is evident in the fiqh issues, while in the texts of hadith and athar, the differences are very minor and mostly in the wording of the versions of Al-Muwatta. They do not change the meaning or its reference, and that the version of Yahya bin Bakir's narration does not come in a lower grade from the other adopted versions of Al-Muwatta where its narrators are considered trusted and cogent. The transactions mentioned in the chapter on sales of Al-Muwatta, whether permitted or forbidden, are still practiced by some people in our time, and are valid in their day to day life, either in the traditional form, or in forms of modern applications.